Factors That Determine the Adhesive Strength in a Bioinspired Bone Tissue Adhesive - Michael Pujari-Palmer; Roger Giró; Philip Procter; Alicja Bojan; Gerard Insley; Håkan Engqvist (ChemEngineering, 2020)
Phosphoserine-modified cements (PMCs) are a family of wet-field tissue adhesives that bond strongly to bone and biomaterials. The present study evaluated variations in the adhesive strength using a scatter plot, failure mode, and a regression analysis of eleven factors. All single-factor, continuous-variable correlations were poor (R2 < 0.25). The linear regression model explained 31.6% of variation in adhesive strength (R2 = 0.316 p < 0.001), with bond thickness predicting an 8.5% reduction in strength per 100 μm increase. Interestingly, PMC adhesive strength was insensitive to surface roughness (Sa 1.27−2.17 μm) and the unevenness (skew) of the adhesive bond (p > 0.167, 0.171, ANOVA). Bone glued in conditions mimicking the operating theatre (e.g., the rapid fixation and minimal fixation force in fluids) produced comparable adhesive strength in laboratory conditions (2.44 vs. 1.96 MPa, p > 0.986). The failure mode correlated strongly with the adhesive strength; low strength PMCs (<1 MPa) failed cohesively, while high strength (>2 MPa) PMCs failed adhesively. Failure occurred at the interface between the amorphous surface layer and the PMC bulk. PMC bonding is sufficient for clinical application, allowing for a wide tolerance in performance conditions while maintaining a minimal bond strength of 1.5−2 MPa to cortical bone and metal surfaces.